Broodstock maintenance technique of koi fish (Cyprinus rubrofuscus, Lacepede 1803) at the Center Fisheries of Freshwater Aquaculture, Sukabumi, West Java - Nafila Junia Azadia; Kismiyati, Kismiyati (Generasi Biologi Indonesia, 2024)
Koi fish (Cyprinus rubrofuscus) is an ornamental fish that has a beautiful body shape and color so it has high economic value. Good maintenance of koi fish parents will produce superior koi fish seeds. The aim of this research is to find out the techniques for raising parent koi fish from preparation to spawning and to find out the problems faced and how to handle them. The methods used in this research are active participation, observation and interviews. The parameters observed include fecundity, FR, HR, and water quality (temperature, pH, and DO). The data obtained from the research was then analyzed descriptively. Based on research that has been carried out, the highest fecundity, FR and HR data obtained during 2 consecutive spawning were 60,480 eggs, 95.8% and 100%. Spawning was carried out semi-artificially using the GnRH hormone with a ratio of the parent's body weight male and female 1:1. The average water quality results measured include a temperature of 23.8 ℃, pH 6.7, and DO 3.2 and are included in optimal conditions for rearing parent koi fish.